1997
DOI: 10.1111/j.1399-302x.1997.tb00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid tolerance and acid‐neutralizing activity of Porphyromonas gingivalis, Prevotella intermedia and Fusobacterium nucleatum

Abstract: The tolerance to acid and the acid-neutralizing activity of three important periodontopathic bacteria, Porphyromonas gingivalis, Prevotella intermedia and Fusobacterium nucleatum were studied. P. gingivalis strains grew only at neutral pH and did not utilize glucose, whereas strains of P. intermedia and F. nucleatum could grow under acidic conditions and increased their growth by utilizing glucose. P. gingivalis tended to raise the culture pH during growth. P. intermedia and F. nucleatum raised the culture pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
104
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 27 publications
13
104
2
Order By: Relevance
“…This study is in accordance with study done by Poplawaska-Kita A et al, who reported that there was an increased risk of periodontitis in patients with diabetes mellitus [21]. Also, the reduction in salivary pH which was evident in our study may increase the growth of periodontal-pathogens which is in accordance with that of Takahashi et al, Fujikawa et al, and Galgut [22][23][24][25].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study is in accordance with study done by Poplawaska-Kita A et al, who reported that there was an increased risk of periodontitis in patients with diabetes mellitus [21]. Also, the reduction in salivary pH which was evident in our study may increase the growth of periodontal-pathogens which is in accordance with that of Takahashi et al, Fujikawa et al, and Galgut [22][23][24][25].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, pH of saliva in patients with periodontitis is more acidic than control group [Table/ Fig-2], which is similar to the study done by Sharmila Baliga et al, who reported that pH of saliva in patients with chronic generalized periodontitis was more acidic than pH of saliva of the control group [3]. This can be explained in accordance with the study conducted by Takahashi et al, that the microorganism which are responsible for periodontitis have a favourable environment for growth in an acidic pH such as P. gingivalis grows at a pH of 6.5-7.0, P. intermedia grows at a pH of 5.0-7.0 and F. nucleatum grows at a pH of 5.5-7.0 [22,23].…”
Section: Discussionsupporting
confidence: 71%
“…2). Although Shah and Williams (47) reported that P. gingivalis had fumarate reductase and produced succinate from aspartate, succinate was not the main end product of this bacterium in our study as well as most previous reports (18,33,54). Acyl-CoA:acetate CoA-transferase was found to convert succinate to succinyl-CoA by using acetyl-CoA as a CoA donor, indicating that a part of succinate derived from aspartate can be readily converted to succinyl-CoA (reaction 7 in Fig.…”
Section: Discussionsupporting
confidence: 36%
“…The perchloric acid-acidified supernatant was diluted with 0.2 N HCl. Carboxylic acids, including formic, acetic, propionic, pyruvic, lactic, malic, succinic, butyric, isobutyric, valeric, and isovaleric acids, were analyzed with a carboxylic acid analyzer (model S-3000X; Tokyo Rikakikai, Tokyo, Japan), as described previously (53,54). Ammonia was assayed enzymatically using glutamate dehydrogenase by the method of Bergmeyer (4).…”
Section: Methodsmentioning
confidence: 99%
“…By adopting a more resilient phenotype through selecting different signalling pathway molecules, in vitro studies demonstrate the survival ‘instincts’ of this pathogen under both poor and sufficient bioavailability of haemin [25,26]. This keystone pathogen with its companion species is associated with the initiation and progression of chronic periodontitis by secretion of several virulence factors including Rgps and PPAD in the periodontal pocket [27,28]. …”
Section: Introductionmentioning
confidence: 99%